2012
DOI: 10.1128/mcb.06311-11
|View full text |Cite
|
Sign up to set email alerts
|

Functional Association between Eyegone and HP1a MediateswinglessTranscriptional Repression during Development

Abstract: The eyegone (eyg) gene encodes Eyg, a transcription factor of the Pax family with multiple roles during Drosophila development. Although Eyg has been shown to act as a repressor, nothing is known about the mechanism by which it represses its target genes. Here, we show that Eyg forms a protein complex with heterochromatin protein 1a (HP1a). Both proteins bind to the same chromatin regions on polytene chromosomes and act cooperatively to suppress variegation and mediate gene silencing. In addition, Eyg binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Thus, boi is negatively regulated by Notch's organizer activity or it at least reflects this activity negatively. Since Eyg encodes a transcriptional repressor [14],[15], it may directly repress boi transcription. This Hh co-receptor does contain a consensus Eyg-binding site for repression (TCACTGA [14]) at position chrX: 2.359.784, although we could not validate the direct binding of Eyg to the boi promoter region by chromatin immunoprecipitation (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, boi is negatively regulated by Notch's organizer activity or it at least reflects this activity negatively. Since Eyg encodes a transcriptional repressor [14],[15], it may directly repress boi transcription. This Hh co-receptor does contain a consensus Eyg-binding site for repression (TCACTGA [14]) at position chrX: 2.359.784, although we could not validate the direct binding of Eyg to the boi promoter region by chromatin immunoprecipitation (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…A similar DV organizer has been found in a variety of contexts, including the fly and vertebrate limbs, although the expression of eyg is restricted to the fly eye. Eyg is functionally related to the human PAX6(5a) oncogene [13] and acts as a transcriptional repressor [14],[15] though complementary patterns of expression of the organizer in developing eyes have never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We found that dH1K27me2 regions are statistically enriched in several TFs binding motifs, some of which have been reported to associate with pericentromeric heterochromatin, such as GAGA factor and the PAX family TF eyegone (eyg) (36,37). While the presence of TEs and repeated sequences was expected, the presence of TF binding motifs was somehow surprising.…”
Section: Discussionmentioning
confidence: 94%
“…We have identified the transcription factor Hth as one of the key factors for transcription-dependent heterochromatin formation throughout embryonic development in Drosophila . A function of transcription factors in heterochromatin formation was first described by our group in Drosophila [ 5 , 7 ], and later confirmed in mouse culture cells [ 6 ]. Hth mutants show overall reduced levels of H3K9me3 and de-condensation of all the constitutive heterochromatin structures analysed.…”
Section: Discussionmentioning
confidence: 98%
“…However, very little is known about the regulation of this non-coding RNA transcription and its phenotypic outcome in a developing organism. Work done in mouse cells and in Drosophila clearly shows that specific transcription factors are involved in the formation of heterochromatin [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%